2002
DOI: 10.4141/a02-021
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and control of Escherichia coli O157:H7 — A review

Abstract: . 2002. Transmission and control of Escherichia coli O157:H7 -A review. Can. J. Anim. Sci. 82: [475][476][477][478][479][480][481][482][483][484][485][486][487][488][489][490]. Escherichia coli 157:H7 has evolved as an important foodborne pathogen since its initial description in 1982. Outbreaks of illness associated with E. coli O157:H7 have been reported throughout the northern hemisphere, most frequently in Canada, the United States, Japan, and the United Kingdom. In Canada, infections due to E. coli O157:H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 147 publications
(139 reference statements)
2
71
1
3
Order By: Relevance
“…Our finding may be in agreement with the existing knowledge which has always implicated cattle as a major reservoir of DEC (Trevena et al, 1999;Bach et al, 2002;Cookson et al, 2006). The presence of typeable DEC serogroups from pastoral cattle was higher in Bluelagoon than Lochinvar.…”
Section: Discussionsupporting
confidence: 82%
“…Our finding may be in agreement with the existing knowledge which has always implicated cattle as a major reservoir of DEC (Trevena et al, 1999;Bach et al, 2002;Cookson et al, 2006). The presence of typeable DEC serogroups from pastoral cattle was higher in Bluelagoon than Lochinvar.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that extensive agriculture can result in an increase in nitrate and phosphorus levels (Jones et al 2001). Similarly, livestock grazing and dairies may increase the presence of fecal bacteria (Bach et al 2002), provoke erosion problems, and increase stream turbidity (Strunk 2003). Conversion of agricultural areas, forests, grass, and wetlands to urban areas leads to large proportional increases in land imperviousness in the form of roofs, sidewalks, roads, parking lots, and turf grass that can dramatically alter the natural hydrologic condition within a watershed (Im et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Enterohemorrhagic strains of Escherichia coli, especially serotype O157:H7, have been linked in humans with hemorrhagic colitis, hemolytic-uremic syndrome, and thrombocytopenic purpura from eating contaminated foods, such as beef and dairy products, vegetables, cider, etc., contaminated drinking water, or contact with colonized animals or animal environments (2,3,17,18). Significant correlations between bovine fecal and hide prevalence with beef carcass contamination indicate a role for controlling E. coli O157 in live cattle (12).…”
mentioning
confidence: 99%